FOR AN ENGAGED ARCHITECTURE - Encarnação Beltrão Spósito, Maria (2010)
Architecture is seen in this paper as a possibility to understand and, above all, to rethink the contemporary world so that we can contribute for the construction of a more equitable future where the differences are respected. From this perspective, an engaged architecture would have always to consider Urbanism so as to understand the city as a level of settling Society’s movement and not only as a scenario where multiple languages are expressed. As it is an essay, the text aims more at raising questions and stimulating debate than at presenting results or answers.